LAMINATED SHEET AND METHOD FOR MANUFACTURING LAMINATED SHEET

JP7642981B2Active Publication Date: 2025-03-11TOPPAN HOLDINGS INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020005347
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-01-16
Publication Date
2025-03-11
Estimated Expiration
2040-01-16

AI Technical Summary

Benefits of technology

【0008】 本開示の態様によれば、高い不燃性や硬度を有しつつ、層間での剥離が生じにくい積層シート及び積層シートの製造方法を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642981000003
    Figure 0007642981000003
  • Figure 0007642981000004
    Figure 0007642981000004
  • Figure 0007642981000005
    Figure 0007642981000005
Patent Text Reader

Abstract

To provide a laminated sheet which prevents peeling between layers while having high non-combustibility and hardness, and a method for producing a laminated sheet.SOLUTION: A laminated sheet 1 includes a raw fabric layer 12 containing a resin material and an inorganic material 12a, a surface protective layer 14 formed on one surface of the raw fabric layer 12, and an anchor layer 16b formed on at least a surface on the side of the surface protective layer 14 of the raw fabric layer 12. In the laminated sheet 1, the raw fabric layer 12 has a first raw fabric layer and a second raw fabric layer, and the surface protective layer 14 may be constituted so as to be formed on the second raw fabric layer. An average particle diameter of the inorganic material 12a is within a range of 1 μm or more and 3 μm or less, and a maximum particle size of the inorganic material 12a is preferably 50 μm or less. A content of the inorganic material in the first raw fabric layer is within a range of 20 mass% or more and 90 mass% or less, and a content of the inorganic material in the second raw fabric layer is preferably within a range of 1 mass% or more and 50 mass% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate sheet and a method for making a laminate sheet. [Background technology]

[0002] 2. Description of the Related Art Conventionally, construction sheets have been proposed in which an inorganic material such as calcium carbonate is highly filled in an original sheet layer for the purpose of improving non-combustibility and hardness (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-132078 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, when other layers such as a surface protection layer are laminated on the surface of an original fabric layer highly filled with inorganic materials, the adhesive strength between the original fabric layer and other layers is weak, and peeling between layers may occur easily, regardless of the lamination method such as lamination method or co-extrusion method. In laminated sheets used as building materials, tape may be applied to and removed from the laminated sheet during construction or use by residents, and the tendency for peeling between layers to occur is problematic.

[0005] The present disclosure has been made in consideration of such problems, and its object is to provide a laminated sheet that has high non-flammability and hardness while being less susceptible to peeling between layers, and a method for manufacturing a laminated sheet. [Means for solving the problem]

[0006] In order to solve the above problems, a laminated sheet according to one embodiment of the present disclosure is characterized in that it comprises an original fabric layer containing a resin material and an inorganic material, a surface protective layer formed on one side of the original fabric layer, and an anchor layer formed on at least the surface of the original fabric layer facing the surface protective layer.

[0007] In addition, a manufacturing method for a laminated sheet according to another aspect of the present disclosure is characterized in that an inorganic material and a resin material are mixed, a resin film containing the inorganic material and the resin material is formed to form an original fabric layer, an anchor material is applied to at least one surface of the original fabric layer to form an anchor layer, and a resin material is applied onto the anchor layer and cured to form a surface protection layer. Effect of the Invention

[0008] According to the aspects of the present disclosure, it is possible to obtain a laminate sheet that has high non-flammability and hardness while being less susceptible to peeling between layers, and a method for manufacturing the laminate sheet. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view showing a configuration example of a laminate sheet according to a first embodiment of the present disclosure. [Diagram 2] FIG. 4 is a cross-sectional view showing a configuration example of a laminate sheet according to a second embodiment of the present disclosure. [Diagram 3] FIG. 4 is a cross-sectional view showing a configuration example of a laminate sheet according to a third embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure will be described below through embodiments, but the following embodiments do not limit the invention according to the claims. In addition, not all of the combinations of features described in the embodiments are necessarily essential to the solution of the invention. In addition, the drawings are schematic diagrams of the invention according to the claims, and the dimensions of the width, thickness, etc. of each part are different from the actual dimensions, and the ratios between these dimensions are also different from the actual dimensions.

[0011] A laminate according to a first embodiment of the present disclosure will be described. The laminate sheet according to the present disclosure is, for example, a laminate sheet applied to a wall surface, fittings, furniture, etc. In the following description, the side of the laminate sheet that contacts the application surface may be referred to as "lower" and the opposite side (front surface) of the laminate sheet that contacts the application surface may be referred to as "upper". Hereinafter, each aspect of each embodiment of the present disclosure will be described with reference to the drawings.

[0012] 1. First embodiment (1.1) Basic structure of laminated sheet Fig. 1 is a cross-sectional view for explaining one configuration example of a laminate sheet 1 according to an embodiment of the present disclosure. As shown in Fig. 1, the laminate sheet 1 includes an adhesive layer 11, an original fabric layer 12, a picture pattern layer 13, and a surface protective layer 14. The laminate sheet 1 is configured by laminating the adhesive layer 11, the original fabric layer 12, the picture pattern layer 13, and the surface protective layer 14 in this order.

[0013] The adhesive layer 11 is a layer provided to improve the adhesion between the laminate sheet 1 and the base to which the laminate sheet 1 is attached. The original fabric layer 12 is a layer that serves as the base material for the laminate sheet 1, and is a layer that absorbs unevenness and steps on the attachment surface to improve the application finish of the laminate sheet 1, and is a layer that gives the laminate sheet 1 fireproofness and hardness. The picture pattern layer 13 is a layer that gives the laminate sheet 1 a desired color and picture pattern. The surface protection layer 14 is a layer provided on the uppermost surface of the laminate sheet 1, and is a layer provided to protect the laminate sheet 1 and adjust the gloss of the surface of the laminate sheet 1. The adhesive layer 11, the base fabric layer 12, the design layer 13 and the surface protective layer 14 will be described in detail below.

[0014] (Original layer) The raw fabric layer 12 is a layer containing one or more types of resin materials and one or more types of inorganic materials. The ratio of the content of the resin material to the inorganic material in the raw fabric layer 12 (resin material:inorganic material) is preferably in the range of 80:20 to 10:90 by mass, and more preferably in the range of 40:60 to 20:80 by mass. That is, the content of the inorganic material relative to the total amount of the resin material and the inorganic material in the raw fabric layer 12 is preferably in the range of 20% by mass to 90% by mass, and more preferably in the range of 60% by mass to 80% by mass.

[0015] When the content is within the above range, there is a tendency for the noncombustibility or flame retardancy of the laminate sheet 1 to be improved. When the content of the inorganic material is within the above range, sufficient surface hardness is obtained, and when the surface of the raw fabric layer 12 is scratched with a Hoffman scratch tester, it is difficult for visible scratches to occur. On the other hand, when the proportion of the resin material is small outside the above-mentioned range, the occurrence of so-called "powdering" on the surface of the original fabric layer 12 can be suppressed when the anchor material to become the anchor layers 16a and 16b is applied to the surface of the original fabric layer 12. In addition, when the ink to become the pattern layer 13 is printed on the surface of the original fabric layer 12, the occurrence of so-called "powdering" on the surface of the original fabric layer 12 can be suppressed. Here, "powdering" refers to the inorganic material contained in the original fabric layer 12 protruding onto the surface of the original fabric layer 12. Furthermore, the lamination suitability is improved when laminating the sheet having the anchor layer 16a or 16b to the original fabric layer 12, and the occurrence of cracks in the folded portion and the peeling of the inorganic material can be suppressed.

[0016] In this way, when the content ratio of the resin material to the inorganic material is within the range of 80:20 to 10:90 by mass, sufficient surface hardness can be obtained while improving the noncombustibility or flame retardancy of the laminate sheet 1. In addition, the lamination suitability of the laminate sheet 1 can be improved, and the occurrence of powdering and cracking can be reduced.

[0017] The inorganic material is preferably surface-treated. For example, the inorganic material is surface-treated using a surface treatment agent such as a saturated fatty acid having 10 to 30 carbon atoms, more preferably a saturated fatty acid having 12 to 26 carbon atoms, an unsaturated fatty acid, or a salt thereof. By surface-treating the inorganic material using such a surface treatment agent, it is possible to suppress aggregation of the inorganic material in the resin material, which is a concern when the inorganic material is highly filled.

[0018] Examples of the saturated fatty acids include palmitic acid, stearic acid, lauric acid, myristic acid, alaic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, and melissic acid, and examples of the salts include sodium salts, potassium salts, magnesium salts, calcium salts, etc. The inorganic material is surface-treated by a known method.

[0019] The inorganic material is preferably in a powder form (powder form), and its average particle size is preferably in the range of 1 μm or more and 3 μm or less, and its maximum particle size is preferably 50 μm or less. If the average particle size and maximum particle size of the inorganic material are within the above-mentioned numerical range, the dispersibility of the inorganic material in the thermoplastic resin can be improved while maintaining the flatness of the surface of the raw fabric layer 12. If the average particle size of the inorganic material is less than 1 μm, the cohesive force between the inorganic materials increases, and the dispersibility in the thermoplastic resin described later may decrease. If the average particle size of the inorganic material exceeds 3 μm, the flatness of the surface of the raw fabric layer 12 may decrease, and the thickness of the anchor layers 16a and 16b described later may become uneven, or unevenness or chipping may occur. If the maximum particle size of the inorganic material exceeds 50 μm, the flatness of the surface of the raw fabric layer 12 may decrease, and the thickness of the anchor layers 16a and 16b described later may become uneven, or unevenness or chipping may occur. In this embodiment, the "average particle size" means the mode diameter.

[0020] The inorganic material preferably includes at least one of antimony trioxide, antimony soda, zircon silicate, zircon oxide, magnesium hydroxide, aluminum hydroxide, basic magnesium carbonate, borax, zinc borate, calcium carbonate, a complex of molybdenum trioxide or antimony dimolybdate with aluminum hydroxide, a complex of antimony trioxide with silica, a complex of antimony trioxide with zinc oxide, zirconium silicic acid, a complex of a zirconium compound with antimony trioxide, and salts thereof, and further silica, alumina, hollow glass beads, and acrylic beads.

[0021] Among them, the inorganic material is preferably a powder containing at least one of calcium carbonate and calcium carbonate salt, for example. Calcium carbonate and calcium carbonate salt are suitable because it is easy to control the particle size and the compatibility with thermoplastic resin. In addition, calcium carbonate and calcium carbonate salt are inexpensive, so they are suitable from the viewpoint of reducing the cost of fire-resistant building materials. In addition, the inorganic material preferably contains calcium carbonate in the range of 50% by mass or more and 100% by mass or less. If the inorganic material contains calcium carbonate in an amount of 50% by mass or more, it can impart sufficient incombustibility or sufficient flame retardancy to the raw fabric layer 12, and can also impart sufficient mechanical strength.

[0022] In addition, the inorganic material may be a powder material having crystallinity, so-called crystalline powder, or a powder material having no crystallinity, so-called amorphous type powder material. If the inorganic material is a powder material having crystallinity, the powder itself is homogeneous and isotropic, so that the mechanical strength of the powder itself tends to be improved, and the scratch resistance and durability of the fireproof building component tend to be improved. In addition, if the inorganic material is an amorphous type powder material, it is possible to appropriately adjust the electrical conductivity and thermal conductivity of the powder itself, or the light transmittance and light absorptance, so that it is possible to impart a design with a wide variety of textures, gloss, etc.

[0023] As the resin material, for example, a thermoplastic resin is used, and includes at least one selected from the group consisting of propylene homopolymer, ethylene homopolymer, ester homopolymer, copolymer of ethylene and / or propylene with other α-olefins copolymerizable therewith, ethylene-ethyl acrylate copolymer, and ethylene-vinyl acetate copolymer. Specifically, polypropylene, polyethylene, polyester, polybutene, polymethylpentene, etc. can be used, and polypropylene, polyethylene, and polyester are preferred, with polypropylene, polyethylene, and polyester being more preferred. By using at least one of polypropylene, polyethylene, and polyester as the thermoplastic resin, the dispersibility of the inorganic material is improved. In addition, by using polypropylene as the thermoplastic resin, the dispersibility of the inorganic material is further improved.

[0024] In addition, the total content of the resin material and the inorganic material is preferably in the range of 90% by mass or more and 100% by mass or less with respect to the mass of the raw fabric layer 12. If the total content of the resin material and the inorganic material is within the above-mentioned numerical range, sufficient non-combustibility or sufficient flame retardancy can be obtained while improving the lamination suitability. If the total content of the resin material and the inorganic material is less than 90% by mass with respect to the mass of the raw fabric layer 12, sufficient non-combustibility or sufficient flame retardancy may not be obtained. In addition, the lamination suitability may decrease, or cracks may occur at the folded portion of the sheet.

[0025] The thickness of the raw fabric layer 12 is preferably in the range of 50 μm to 12500 μm, more preferably in the range of 70 μm to 10000 μm. If the thickness of the raw fabric layer 12 is within the above-mentioned numerical range, the lamination suitability can be improved. If the thickness of the raw fabric layer 12 is less than 50 μm, the lamination suitability tends to decrease. In addition, if the thickness of the raw fabric layer 12 exceeds 12500 μm, it becomes difficult to handle in terms of processability and workability.

[0026] The raw fabric layer 12 is formed by uniaxial or biaxial stretching. In this case, as shown in Fig. 1, the raw fabric layer 12 has voids 12b formed between the inorganic material 12a and the resin material and having a planar (horizontal) shape extending in a direction parallel to the front and back surfaces of the raw fabric layer 12. A plurality of voids 12b are scattered throughout the raw fabric layer 12.

[0027] The raw fabric layer 12 of this embodiment may be formed by adding a foaming agent to the resin material and the inorganic material. This allows voids to be formed in the raw fabric layer 12 in a shape extending in the thickness direction of the raw fabric layer 12. The voids formed by the foaming agent are connected to each other, and become larger than voids formed by the foaming agent alone. Therefore, the laminated sheet 1 including the raw fabric layer 12 having such voids scattered throughout has even higher heat insulation properties.

[0028] The foaming agent may be at least one of decomposition gas generating foaming agents, expandable capsule foaming agents, etc. Preferred examples of the decomposition gas generating foaming agent include at least one of azodicarbonamide, dinitrosopentamethylenetetramine, p-toluenesulfonylhydrazide, benzenesulfonylhydrazide, sodium bicarbonate and ammonium carbonate, azobisisobutyronitrile, 4,4-oxybis(benzenesulfonic acid hydrazide), diphenylsulfone-3,3'-disulfohydrazide, benzene-1,3-disulfohydrazide, p-toluenesulfonylsemicarbazide, and expandable hollow microspheres. Examples of expandable capsule foaming agents include those in which a volatile expanding component of a hydrocarbon such as ethane, butane, pentane, neopentane, hexane, or heptane is encapsulated in fine particles coated with a resin material such as acrylic ester, vinylidene chloride, acrylonitrile, or urethane.

[0029] The raw fabric layer 12 formed from a mixture containing an inorganic material, a resin material, and a foaming agent has a plurality of voids formed by the foaming agent scattered throughout the raw fabric layer 12 . The content of the foaming agent may be adjusted as necessary as long as it can provide heat insulation as a building material and has the interlaminar strength of the resin composition and the strength as a building material. For example, the amount of the foaming agent may be adjusted so that the foaming agent is foamed to at least 10%, 25%, 50%, 100%, 150%, 200% or more of the volume when the raw fabric layer 12 is heated. The content of the foaming agent is, for example, in the range of 5% by mass or more and 10% by mass or less with respect to the mass of the raw fabric layer 12.

[0030] In addition, when the raw fabric layer 12 is formed by uniaxially or biaxially stretching a mixture containing a foaming agent, the raw fabric layer 12 has voids extending in the thickness direction due to the foaming agent regardless of the position of the inorganic material 12a. As a result, the raw fabric layer 12 has voids 12b extending in the horizontal direction in FIG. 1 around the inorganic material 12a, and as a result, a raw fabric layer 12 having a plurality of voids 12b extending in the horizontal direction in FIG. 1 scattered throughout can be obtained. The raw fabric layer 12 having such three-dimensional voids 12b formed therein can enhance the heat insulating effect.

[0031] Anchor layers 16a and 16b are provided on both sides of the raw fabric layer 12. The anchor layers 16a and 16b will be described later. It is preferable to perform a surface treatment such as a corona treatment or a plasma treatment on both sides of the raw fabric layer 12 before forming the anchor layers 16a and 16b described later. By performing a surface treatment such as a corona treatment or a plasma treatment on both sides of the raw fabric layer 12, the adhesiveness (adhesion) between the anchor layers 16a and 16b formed on the surface-treated sides and the raw fabric layer 12 is improved. Also, before forming the anchor layers 16a and 16b, both sides of the raw fabric layer 12 may be brushed to remove any dusted inorganic material in advance.

[0032] (Anchor layer) The anchor layers 16a and 16b are layers formed to cover the entire surface of the original fabric layer 12, and are layers for preventing the inorganic material contained in the original fabric layer 12 from powdering off. The inorganic material contained in the original fabric layer 12 may powder off in the printing system, specifically in the printing device, when the picture pattern layer 13 is formed (when ink is printed) or when the surface protective layer 14 is formed (when resin is applied), and may contaminate the printing system. In addition, if the inorganic material contained in the original fabric layer 12 powders off, defects such as ink loss may occur in the picture pattern layer 13. Here, "ink loss" refers to ink not being printed partially.

[0033] The anchor layer 16b also has a function of improving adhesion between the original fabric layer 12 and the ink forming the picture pattern layer 13 or the resin material forming the surface protection layer 14. If the anchor layer 16b is not provided on the upper surface of the original fabric layer 12, the ink or resin material may not adhere to the original fabric layer 12 and may peel off.

[0034] Such anchor layers 16a and 16b preferably contain a urethane resin containing vinyl chloride acetate or an acrylic resin containing vinyl chloride acetate. Here, "vinyl chloride acetate" means a copolymer of vinyl chloride and vinyl acetate. Furthermore, "urethane resin containing vinyl chloride acetate" means a composition containing vinyl chloride acetate and a urethane resin, and "acrylic resin containing vinyl chloride acetate" means a composition containing vinyl chloride acetate and an acrylic resin. The ratio of the vinyl chloride acetate content to the urethane resin or acrylic resin content (vinyl chloride acetate content: urethane resin or acrylic resin content) is preferably within the range of 80:20 to 1:99 by mass, more preferably within the range of 50:50 to 5:95, and even more preferably within the range of 20:80 to 10:90.

[0035] In addition, the "urethane resin containing vinyl chloride acetate" and the "urethane resin containing vinyl chloride acetate" may contain a curing agent in addition to the vinyl chloride acetate and urethane resin or acrylic resin described above. The curing agent is added to ensure that the urethane resin containing vinyl chloride acetate or the acrylic resin containing vinyl chloride acetate is cured, and the content of the curing agent is not particularly limited. For example, the ratio of the content of the urethane resin or acrylic resin containing vinyl chloride acetate to the content of the curing agent (content of the urethane resin or acrylic resin containing vinyl chloride acetate: content of the curing agent) may be within a range of 99:1 to 1:99 by mass ratio, preferably within a range of 99:1 to 50:50, and more preferably within a range of 95:5 to 90:10.

[0036] The content of the urethane resin containing vinyl chloride acetate or the acrylic resin containing vinyl chloride acetate in the anchor layers 16a and 16b (hereinafter sometimes referred to as the resin content) is preferably in the range of 15% by mass to 100% by mass, more preferably in the range of 80% by mass to 100% by mass, and even more preferably in the range of 85% by mass to 95% by mass, based on the mass of the anchor layers 16a and 16b. When the resin content is within the above-mentioned numerical range, the anchor layers 16a and 16b can be formed uniformly without unevenness or chipping while ensuring sufficient interlayer strength between the base fabric layer 12 and the picture pattern layer 13 or the surface protection layer 14.

[0037] On the other hand, if the resin content is less than 15% by mass, the interlayer strength may be insufficient. If the resin content is less than 80% by mass, there is no problem in use, but the bite ratio of the anchor layers 16a and 16b into the original fabric layer 12 decreases. Therefore, the interlayer strength between the anchor layers 16a and 16b and the original fabric layer 12 may decrease slightly.

[0038] If the resin content in the anchor layers 16a and 16b is 100% by mass or less with respect to the mass of the anchor layers 16a and 16b, there is no problem in use. However, if the resin content exceeds 95% by mass, more precisely 98% by mass, the anchor layers 16a and 16b may be chipped due to insufficient hardening. In addition, the interlayer strength between the anchor layers 16a, 16b and the base fabric layer 12 or between the anchor layer 16b and the picture pattern layer 13 may decrease.

[0039] In addition, it is preferable that the resin content in the anchor layers 16a and 16b provided on both sides of the raw fabric layer 12 is the same. In this case, it is possible to reduce the occurrence of distortion, warping, etc. of the raw fabric layer 12, and as a result, it is possible to reduce the occurrence of distortion, warping, etc. of the entire laminate sheet 1. In addition, since the coating liquid for forming the anchor layers 16a and 16b can be made common, it is possible to reduce manufacturing costs and improve work efficiency.

[0040] The thickness of the anchor layers 16a and 16b is, for example, in the range of 0.5 μm to 20 μm, preferably in the range of 0.5 μm to 10 μm. The thickness of the anchor layers 16a and 16b is preferably the same as each other. When the thickness of the anchor layers 16a and 16b is the same, the physical properties of the anchor layers 16a and 16b are almost the same, so that the occurrence of distortion, warping, etc. of the raw fabric layer 12 can be reduced.

[0041] In the case of the extrusion lamination method, the anchor layers 16a and 16b may be formed by co-extruding a thermal adhesive resin such as a maleic acid modified olefin resin together with the raw fabric layer 12 to improve the interlayer adhesion between the raw fabric layer 12 and the anchor layers 16a and 16b. In addition, when the adhesive layer 11 is not provided on the back surface of the original fabric layer 12, the anchor layer 16a may not be provided on the back surface of the original fabric layer 12 (the back surface of the laminated sheet 1). This is because there is no problem even if the back surface of the laminated sheet 1 does not have an anchor layer depending on the application method of the laminated sheet 1 to the base.

[0042] (Pattern layer) The picture design layer 13 is formed on the raw fabric layer 12 and is a layer that imparts a picture design to the laminated sheet 1 to give it a design. There is no particular restriction on the type of the picture pattern formed by the picture pattern layer 13, and for example, a wood grain pattern, a stone pattern, a fabric pattern, an abstract pattern, a geometric figure, a character, a symbol, etc. may be formed alone or in combination of two or more kinds. The picture pattern layer 13 may also be a layer imparted with a single color.

[0043] The picture pattern layer 13 is a layer formed by printing with, for example, a urethane resin-based ink. For example, the urethane resin-based ink may contain a urethane resin, a vinyl chloride-vinyl acetate copolymer resin, an organic pigment, and an inorganic pigment. The composition of the picture pattern layer 13 preferably contains, for example, a urethane resin in the range of 50.9% by mass to 76.7% by mass, a vinyl chloride-vinyl acetate copolymer resin in the range of 10.2% by mass to 23.3% by mass, an organic pigment in the range of 0% by mass to 37.7% by mass, and an inorganic pigment in the range of 0% by mass to 20.0% by mass.

[0044] The picture pattern layer 13 can be formed by any printing method, such as inkjet printing, gravure printing, screen printing, offset printing, or flexographic printing. The mass of the picture pattern layer 13 is, for example, 8.36 [g / m 2 ] or less (solid amount) (organic mass 6.71[g / m 2 ] or less). The ratio of the formation area (ink printing area) per unit area (e.g., 300 mm square) of the picture pattern layer 13 is preferably 50% or less, and more preferably 90% or more. In particular, when the picture pattern layer 13 is a layer formed by solid printing, the ratio of the formation area (area covered by ink) per unit area of ​​the picture pattern layer 13 is preferably 90% or less. The unit area is not limited to 300 mm square, and may be, for example, 200 mm square or more and 400 mm square or less. The unit area of ​​the picture pattern layer 13 is specified to ensure an appropriate light transmittance, and may be set based on, for example, the location where the laminated sheet 1 is placed and the brightness of the light source.

[0045] (Surface protective layer) The surface protective layer 14 is formed on the picture pattern layer 13, and is a layer for protecting the surface of the laminate sheet 1. The surface protective layer 14 is preferably a transparent layer so that the picture and color of the picture pattern layer 13 are expressed on the surface of the laminate sheet 1. The surface protective layer 14 may be, for example, a top coat layer or an upper base resin layer.

[0046] When the laminate sheet 1 is used for interior decoration, the surface protective layer 14 is formed by applying a coating resin onto the picture pattern layer 13 in order to produce a visual gloss matte effect on the surface of the laminate sheet 1. The coating resin may be a urethane resin, an acrylic resin, an ultraviolet curable resin, an ionizing radiation curable resin, or the like, depending on the required performance. The surface protective layer 14 is formed by applying the coating resin in a single layer or multiple layers. When the surface protective layer 14 is formed in multiple layers, different coating resins may be applied in two or more layers, or the same resin may be applied in two or more layers.

[0047] Even if the laminate sheet 1 is used for interior decoration, if the laminate sheet 1 requires abrasion resistance or scratch resistance, the surface protection layer 14 is formed by applying a thermoplastic resin or the like onto the picture design layer 13. In this case, the design can be improved by providing an uneven pattern on the surface of the surface protection layer 14. Examples of the uneven pattern include duct grooves on a wood grain board, uneven surfaces on a stone slab (such as granite cleavage surfaces), textures on a cloth surface, matte finish, sand grain, hairlines, and the like. As a method for forming the uneven pattern, for example, an embossing method using a known sheet-fed or rotary embossing machine can be adopted.

[0048] In order to stably maintain performance such as scratch resistance and abrasion resistance, and in consideration of bending processability and economic efficiency, the thickness of the surface protective layer 14 is preferably 60 μm or more and 200 μm or less, and more preferably 60 μm or more and 150 μm or less. When the laminate sheet 1 is used for exterior applications, it is preferable to add an ultraviolet absorber such as a benzotriazole-based, benzoate-based, benzophenone-based, or triazine-based agent, and a light stabilizer such as a hindered amine-based agent to the surface protective layer 14.

[0049] (Adhesive layer) The adhesive layer 11 has a function of ensuring adhesion to the base to which the laminate sheet 1 is attached. The thickness of the adhesive layer 11 is preferably within a range of, for example, 0.1 μm to 3.0 μm. By making the thickness of the adhesive layer 11 within the above-mentioned range, it is possible to increase the adhesion to the base and to prevent the adhesive layer 11 from protruding from the laminate sheet 1 when the laminate sheet 1 is attached.

[0050] The material constituting the adhesive layer 11 is not particularly limited, but can be appropriately selected from adhesive resins such as acrylic, polyester, polyurethane, and epoxy resins. The coating method can be appropriately selected depending on the viscosity of the adhesive resin, and for example, gravure coating is used.

[0051] The adhesive layer 11 may be a primer. In this case, the material constituting the adhesive layer 11 may be, for example, a binder such as nitrocellulose, cellulose, vinyl chloride-vinyl acetate copolymer, polyvinyl butyral, polyurethane, acrylic, polyester, etc., either alone or modified. These may be in any form, such as water-based, solvent-based, or emulsion type. The curing method may also be selected from a one-liquid type that cures alone, a two-liquid type that uses a curing agent in combination with a base agent, or a type that cures by irradiation with ultraviolet rays or electron beams. A two-liquid type that cures by combining an isocyanate-based curing agent with a urethane-based base agent is generally used as a curing method, and this method is suitable from the viewpoints of workability, cost, and cohesive force of the resin itself. In addition to the above binders, colorants such as pigments and dyes, extender pigments, solvents, various additives, inorganic fillers, etc. may be added.

[0052] In particular, the adhesive layer 11 preferably contains an inorganic filler such as silica, alumina, magnesia, titanium oxide, barium sulfate, etc. The adhesive layer 11 is located on the back surface of the laminated sheet 1. For this reason, considering that the laminated sheet 1 is wound up as a continuous plastic film (web-like), it is necessary to prevent the films from adhering to each other, making them difficult to slide, or from causing blocking, such as preventing them from being peeled off. By including an inorganic filler in the adhesive layer 11, it is possible to suppress adhesion and blocking between the laminated sheets (films).

[0053] The adhesive layer 11 does not necessarily have to be provided. This is because there is no problem if the adhesive layer 11 is not provided on the back surface of the laminated sheet 1 depending on the application method of the laminated sheet 1 to the base, etc.

[0054] (1.2) Manufacturing method of laminated sheet An example of a method for producing the laminate sheet 1 will now be described. First, the raw fabric layer 12 is formed. The inorganic material and the resin material contained in the raw fabric layer 12 are mixed using a known mixer such as a super mixer, a Henschel mixer, a tumbler mixer, or a ribbon blender. The inorganic material and the resin material are heated and kneaded, and the mixture of the components contained in the raw fabric layer 12 is extruded using a known molding machine such as a T-die extruder to form a resin film containing the inorganic material and the resin material. The formed resin film is then stretched uniaxially or biaxially using a single-screw extruder or a twin-screw extruder to form the raw fabric layer 12 having a uniform micropore size.

[0055] The anchor layers 16a and 16b are formed by applying an anchor material to the lower and upper surfaces of the raw fabric layer 12. At this time, the anchor layers 16a and 16b may be formed simultaneously on both surfaces of the raw fabric layer 12, or the anchor layer 16a may be formed on the lower surface of the raw fabric layer 12, and the anchor layer 16b may be formed on the upper surface of the raw fabric layer 12 at a timing different from that of the anchor layer 16a. For example, a urethane resin-based ink is applied to the upper surface of the raw fabric layer 12 (the surface of the anchor layer 16b) in a desired pattern, and then dried to form the pattern layer 13. A resin material such as a coating resin or a thermoplastic resin is applied onto the surface of the picture design layer 13 and cured to form the surface protection layer 14.

[0056] Next, the adhesive layer 11 is formed by applying, for example, an adhesive resin or a primer to the lower surface of the raw fabric layer 12 (the surface of the anchor layer 16a). In this manner, the laminate sheet 1 according to the present embodiment is manufactured. When the anchor layers 16a and 16b are formed at different times, the anchor layer 16a may be formed after the surface protective layer 14 is formed, and then the adhesive layer 11 may be formed.

[0057] (1.3) Effects of the First Embodiment The laminate sheet as described above has the following effects. (1) The laminate sheet of the present embodiment contains inorganic particles in the original fabric layer and has an anchor layer on the surface of the original fabric layer. According to this configuration, the flame retardancy and sheet hardness of the laminated sheet are improved, and the interlayer adhesion between the original fabric layer and the layer (pattern printed layer, surface protection layer) provided on the surface of the original fabric layer is improved, making it difficult for the layers to peel off from each other.

[0058] (2) The laminate sheet of the present embodiment has a plurality of voids formed around the inorganic material in the original fabric layer, and the voids are scattered throughout the original fabric layer. According to this configuration, three-dimensional voids are formed within the original fabric layer, thereby improving the heat insulating effect.

[0059] (3) In the laminate sheet of the present embodiment, the inorganic material contained in the original layer preferably has an average particle size in the range of 1 μm to 3 μm, and a maximum particle size of the inorganic material is preferably 50 μm or less. According to this configuration, the surface of the original film layer can be flattened, and the occurrence of unevenness and chipping in the original film layer can be suppressed.

[0060] (4) In the laminate sheet of the present embodiment, the content of the inorganic material in the original layer is preferably in the range of 20% by mass or more and 90% by mass or less based on the total amount of the resin material and the inorganic material. According to this configuration, the noncombustibility and sheet hardness of the laminated sheet can be improved, and the smoothness and processability of the surface of the original fabric layer can be improved.

[0061] (5) In the laminate sheet of the present embodiment, it is preferable to use calcium carbonate or a calcium carbonate salt as the inorganic particles. This configuration makes it easy to control the particle size of the inorganic particles and the compatibility with the thermoplastic resin, and is also preferable from the viewpoint of reducing the cost of the laminate sheet.

[0062] 2. Second embodiment Hereinafter, the laminate sheet according to the second embodiment of the present disclosure will be described with reference to FIG. FIG. 2 is a cross-sectional view for illustrating one configuration example of a laminate sheet 2 according to a second embodiment of the present disclosure.

[0063] The laminated sheet 2 includes an adhesive layer 11, an original fabric layer 22 having a first original fabric layer 22a and a second original fabric layer 22b, a picture pattern layer 13, and a surface protective layer 14. The laminated sheet 2 is configured by laminating the adhesive layer 11, the first original fabric layer 22a, the second original fabric layer 22b, the picture pattern layer 13, and the surface protective layer 14 in this order. The picture pattern layer 13 and the surface protective layer 14 are formed on the surface of the second original fabric layer 22b. That is, the laminated sheet 2 is different from the laminated sheet 1 according to the first embodiment in that the laminated sheet 2 includes an original fabric layer 22 having a first original fabric layer 22a and a second original fabric layer 22b instead of the original fabric layer 12.

[0064] The first raw fabric layer 22a and the second raw fabric layer 22b will be described below. Note that the layers other than the first raw fabric layer 22a and the second raw fabric layer 22b (the adhesive layer 11, the picture pattern layer 13, and the surface protective layer 14) have the same configuration as the layers of the laminated sheet 1, and therefore the description thereof will be omitted.

[0065] (2.1) Basic structure of laminated sheet <First fabric layer, second fabric layer> The first raw fabric layer 22a has the same configuration as the raw fabric layer 12 described in the first embodiment. Anchor layers 26a and 26b are provided on both sides of the first raw fabric layer 22a. The second raw fabric layer 22b is a layer containing one or more types of resin materials and one or more types of inorganic materials. The content of the inorganic material in the second raw fabric layer 22b is preferably less than the content of the inorganic material in the second raw fabric layer 22b. The content ratio of the resin material to the inorganic material in the second raw fabric layer 22b (resin material:inorganic material) is preferably in the range of 99:1 to 50:50 by mass ratio, and more preferably in the range of 90:10 to 60:40 by mass ratio. That is, the content of the inorganic material relative to the total amount of the resin material and the inorganic material in the second raw fabric layer 22b is preferably in the range of 1% by mass to 50% by mass, and more preferably in the range of 10% by mass to 40% by mass.

[0066] It is preferable to use the same material as the raw fabric layer 12 as the inorganic material. In addition, it is preferable to use at least one of calcium carbonate and calcium carbonate salt as the inorganic material for the first raw fabric layer 22a. And it is preferable to use an inorganic material different from the inorganic material contained in the first raw fabric layer 22a for the second raw fabric layer 22b. For example, when the first raw fabric layer 22a contains at least one of calcium carbonate and calcium carbonate salt as the inorganic material, it is preferable that the second raw fabric layer 22b contains at least one of calcium carbonate and inorganic material other than calcium carbonate as the inorganic material. This allows the first raw fabric layer 22a to contain inorganic particles while reducing the manufacturing cost of the first raw fabric layer 22a. Also, the second raw fabric layer 22b can improve non-combustibility and sheet hardness.

[0067] The thickness of the second raw fabric layer 22b is preferably equal to or thinner than that of the first raw fabric layer 22a. Specifically, the ratio of the thickness of the first raw fabric layer 22a to that of the second raw fabric layer 22b is preferably 50:50 to 95:5. In this case, the decrease in the non-combustibility and sheet hardness of the laminated sheet 2 can be suppressed.

[0068] As shown in Fig. 2, anchor layers 26c and 26d are provided on both sides of the second original fabric layer 22b. It is preferable to perform surface treatment such as corona treatment or plasma treatment on both sides of the second original fabric layer 22b before forming the anchor layers 26c and 26d. The anchor layer 26c is a layer provided on the lower surface of the second original fabric layer 22b, and the anchor layer 26d is a layer provided on the upper surface of the second original fabric layer 22b. The anchor layers 26c and 26d have the same configuration as the anchor layers 26a and 26b described in the first embodiment.

[0069] (2.2) Effects of the Second Embodiment The laminate sheet as described above has the following effects in addition to the effects described in the first embodiment. (6) The laminate sheet of the present embodiment has a first raw fabric layer and a second raw fabric layer each containing different inorganic particles. According to this configuration, the flame retardancy and sheet hardness of the laminated sheet can be further improved, and the interlayer adhesion between the original fabric layer and the layer (pattern printed layer, surface protection layer) provided on the surface of the original fabric layer can be improved, making it difficult for the layers to peel off from each other.

[0070] 3. Third embodiment Hereinafter, a laminate sheet according to a third embodiment of the present disclosure will be described with reference to FIG. FIG. 3 is a cross-sectional view for explaining one configuration example of a laminate sheet 3 according to a third embodiment of the present disclosure.

[0071] The laminated sheet 3 includes an adhesive layer 11, an original fabric layer 22 having a first original fabric layer 22a and a second original fabric layer 22b, a design layer 13, and a surface protective layer 14 having an upper base resin layer 34a, a first topcoat layer 34b, and a second topcoat layer 34c. The laminated sheet 2 is configured by laminating the adhesive layer 11, the first original fabric layer 22a, the second original fabric layer 22b, the design layer 13, the upper base resin layer 34a, the first topcoat layer 34b, and the second topcoat layer 34c in this order. That is, the laminated sheet 2 is different from the laminated sheet 1 according to the first embodiment in that the laminated sheet 2 includes a surface protective layer 34 having an upper base resin layer 34a, a first topcoat layer 34b, and a second topcoat layer 34c instead of the surface protective layer 14.

[0072] The first raw fabric layer 22a and the second raw fabric layer 22b will be described below. Note that the layers other than the surface protective layer 34 (the adhesive layer 11, the first raw fabric layer 22a, the second raw fabric layer 22b, and the picture pattern layer 13) have the same configuration as the layers of the laminated sheet 2, and therefore the description thereof will be omitted.

[0073] (3.1) Basic structure of laminated sheet <Surface protective layer> The surface protective layer 34 includes an upper base resin layer 34a, a first top coat layer 34b, and a second top coat layer 34c. As shown in Fig. 3, the surface protective layer 34 may have an embossed shape.

[0074] The upper base resin layer 34a is a layer intended for shock absorption (buffering), etc., and is also an adhesive layer for bonding the picture pattern layer 13 and the first top coat layer 34b. The upper base resin layer 34a also has the function of making the picture pattern layer 13 clearer when forming the picture pattern layer 13, and improving the scratch resistance of the picture pattern layer 13. The upper base resin layer 34a is formed, for example, from a polypropylene resin having transparency. The thickness of the upper base resin layer 34a is, for example, about 150 μm or more and 200 μm or less.

[0075] The first topcoat layer 34b is a topcoat layer intended for adjusting the gloss and / or protecting the picture pattern layer 13. The first topcoat layer 34b is preferably formed of, for example, an ultraviolet-curable resin. The thickness of the surface protection layer 34 is preferably, for example, 0.1 μm or more and 15 μm or less.

[0076] The second topcoat layer 34c is a layer partially provided on the surface side of the first topcoat layer 34b, and covers a part of the surface of the first topcoat layer 34b. An example of the part of the surface of the first topcoat layer 34b is a part facing the pattern of the picture pattern layer 13. The material of the second topcoat layer 34c can be the same resin as that of the first topcoat layer 34b. A filler may be added to the second topcoat layer 34c. By adding a filler, it is possible to impart mechanical properties such as gloss, touch, texture, surface strength, and friction different from those of the first topcoat layer 34b. As the filler, for example, a material that consumes less oxygen during combustion is preferable, and examples thereof include calcium carbonate, antimony trioxide, antimony soda, zirconium compounds such as zirconium silicate and zirconium oxide, magnesium hydroxide, aluminum hydroxide, basic magnesium carbonate, borax, zinc borate, complexes of molybdenum trioxide or antimony dimolybdate and aluminum hydroxide, complexes of antimony trioxide and silica, complexes of antimony trioxide and zinc oxide, silicic acid of zirconium, complexes of zirconium compounds and antimony trioxide, etc. In particular, calcium carbonate is suitable from the viewpoint of reducing the cost of decorative sheets, since it is easy to control the particle size by the manufacturing method and the compatibility with polyolefin resin by surface treatment, and the material cost is also inexpensive. In addition, beads or irregular particles of resins such as acrylic, polyolefin, and silicone, and beads or irregular particles of inorganic substances such as silica (especially hollow silica), alumina, and metal oxides can be used. In addition, the method of forming the second topcoat layer 34c is not particularly limited, and known printing methods can be adopted. The second topcoat layer 34c is also generally referred to as a "touch-sensitive coating layer" or a "matte conduit printing layer."

[0077] The surface protection layer 34 has an embossed shape consisting of recesses and protrusions in sync with the pattern of the picture pattern layer 13, for example, so that a three-dimensional feel can be imparted to the touch. The deviation between the embossed shape and the pattern of the picture pattern layer 13 is preferably within a range of, for example, 10 mm or less in the longitudinal direction and 3 mm or less in the transverse direction (width direction) of the shape of the picture pattern. For example, when the picture pattern is wood grain, the direction in which the conduits of the wood grain extend is the "longitudinal direction of the shape of the picture pattern", and the direction perpendicular to the longitudinal direction is the "transverse direction of the shape of the picture pattern". In particular, when the conduits of the wood grain extend along the longitudinal direction of the laminated sheet 3, the longitudinal direction of the laminated sheet 3 is the "longitudinal direction of the shape of the picture pattern", and the transverse direction (width direction) of the laminated sheet 3 is the "transverse direction of the shape of the picture pattern". Since the surface protective layer 34 is transparent, the embossed shape is first strongly visible due to the reflection of oblique light, but if the deviation between the embossed shape and the pattern of the picture pattern layer 13 is within the above range, it is difficult to visually recognize the reflected light and the transmitted light of the picture pattern layer 13 at the same time, so there is no sense of incongruity. By suppressing the deviation between the embossed shape and the pattern of the picture pattern layer 13 within a certain range, a laminated sheet 3 can be obtained in which the pattern shape and distribution are equal and matched accurately over the entire surface of the sheet. The height difference between the recesses and protrusions of the embossed shape is preferably, for example, within a range of 3 μm to 200 μm. The height difference between the recesses and protrusions can be selected to a value suitable for the design of the laminated sheet 3 to be desired. For example, a continuous multi-step shape can be obtained within the maximum height difference (200 μm). In particular, in order to obtain a shape as a macroscopic three-dimensional object, the height difference is more preferably in a range of 10 μm to 150 μm.

[0078] (3.2) Effects of the Third Embodiment The laminate sheet as described above has the following effects in addition to the effects described in the first and second embodiments. (7) The laminate sheet of this embodiment has an embossed shape and a second top coat layer provided in a portion facing the picture pattern of the picture design layer. According to this configuration, a three-dimensional feel can be imparted to the surface of the laminated sheet. EXAMPLES

[0079] The laminate sheet according to the present disclosure will be described below with reference to examples. In the lamination examples, laminate sheets having the configurations described in the following Examples and Comparative Examples were prepared and attached to a floor material to evaluate the laminate sheets.

[0080] <Example 1> In Example 1, the raw fabric layers form a single laminated sheet. First, calcium carbonate with an average particle size of 2 μm and a maximum particle size of 30 μm as an inorganic material for the raw layer and polypropylene as a resin material were mixed using a super mixer. At this time, the calcium carbonate content relative to the total amount of calcium carbonate and polypropylene was 50 mass%. Next, the calcium carbonate and polypropylene were heated and kneaded, and the mixture was extruded using a T-die extruder to form a polypropylene film. Next, the formed polypropylene film was biaxially stretched using a twin-screw extruder to form a raw layer with a thickness of 400 μm having a uniform micropore size around the calcium carbonate.

[0081] A urethane resin containing vinyl chloride and acetate was applied to both sides of the original layer and dried to form an anchor layer with a thickness of 5 μm. Next, a urethane resin ink was applied to the top surface of the original layer (the surface of the anchor layer) and dried to form a picture pattern layer. Polyethylene was applied as a thermoplastic resin onto the surface of the design layer and cured to form a thermoplastic resin layer, and then an acrylic resin was applied as a coating resin and cured to form a coating layer, forming a surface protection layer with a thickness of 100 μm.

[0082] Next, an adhesive resin was applied to the lower surface of the original layer (the surface of the anchor layer) to form an adhesive layer having a thickness of 1.0 μm. In this manner, the laminate sheet of Example 1 was produced.

[0083] <Example 2> A base fabric layer was formed in the same manner as in Example 1 to serve as a first base fabric layer. In addition, a second original layer was prepared in the same manner as the original layer in Example 1, except that silica with an average particle size of 2 μm and a maximum particle size of 30 μm was used as the inorganic material, and polypropylene was used as the resin material, and the content of silica relative to the total amount of silica and polypropylene was 40 mass%. At this time, the film thickness of the first original layer and the second original layer was adjusted so that the film thickness ratio of the first original layer and the second original layer was 60:40. Next, the first and second raw fabric layers were laminated together via the molten polyethylene. Next, a picture pattern layer and a surface protection layer were formed on the upper surface of the second raw fabric layer in the same manner as in Example 1, and an adhesive layer was formed on the lower surface of the first raw fabric layer in the same manner as in Example 1. In this manner, a laminate sheet of Example 2 in which the original fabric layer was composed of the first original fabric layer and the second original fabric layer was produced.

[0084] <Example 3> A laminate sheet of Example 3 was produced in the same manner as in Example 2, except that the thermoplastic resin layer was not formed when the surface protective layer was formed.

[0085] <Example 4> A laminate sheet of Example 4 was produced in the same manner as in Example 2, except that the average particle size of calcium carbonate used in the first raw sheet layer was 4 μm and the maximum particle size was 50 μm.

[0086] <Example 5> A laminate sheet of Example 5 was produced in the same manner as in Example 2, except that the content of calcium carbonate used in the first raw fabric layer was 95 mass % based on the total amount of calcium carbonate and polypropylene.

[0087] <Example 6> A laminate sheet of Example 6 was produced in the same manner as in Example 2, except that the content of calcium carbonate used in the first raw layer was 15 mass % based on the total amount of calcium carbonate and polypropylene.

[0088] <Example 7> A laminate sheet of Example 7 was produced in the same manner as in Example 2, except that the average particle size of calcium carbonate used in the second raw sheet layer was 5 μm and the maximum particle size was 50 μm.

[0089] <Example 8> A laminate sheet of Example 8 was produced in the same manner as in Example 2, except that the content of calcium carbonate used in the second raw fabric layer was 60 mass % based on the total amount of calcium carbonate and polypropylene.

[0090] <Example 9> A laminated sheet of Example 9 was produced in the same manner as in Example 2, except that the ratio of the thickness of the first raw fabric layer to the second raw fabric layer was 25:75. At this time, the total thickness of the first raw fabric layer and the second raw fabric layer was kept the same as in Example 2.

[0091] <Comparative Example 1> A laminate sheet of Comparative Example 1 was produced in the same manner as in Example 2, except that the first raw fabric layer was formed using urethane beads having an average particle size of 2 μm and a maximum particle size of 30 μm instead of calcium carbonate.

[0092] <Comparative Example 2> A laminate sheet of Comparative Example 2 was produced in the same manner as in Example 2, except that the second raw fabric layer was formed using aramid fiber instead of silica.

[0093] <Comparative Example 3> A laminate sheet of Comparative Example 3 was produced in the same manner as in Example 2, except that the second base layer was formed using urethane beads having an average particle size of 2 μm and a maximum particle size of 30 μm instead of silica.

[0094] <Comparative Example 4> A laminate sheet of Comparative Example 3 was produced in the same manner as in Example 2, except that no anchor layer was provided on the surfaces of the first and second original fabric layers.

[0095] [evaluation] (a) Interlayer adhesion The adhesion between the layers constituting the laminated sheet of each Example and Comparative Example was evaluated by an adhesion (cross-cut method) test in accordance with JIS K 5600-5-6. In the test, the case where the number of peeled squares was 0 to 2 was evaluated as "○", the case where the number of peeled squares was 3 to 5 was evaluated as "△", and the case where the number of peeled squares was 6 or more was evaluated as "×".

[0096] (b) Nonflammable The non-combustibility of the laminated sheets of each Example and Comparative Example was evaluated by a heat generation test using a cone calorimeter tester conforming to ISO5660-1. In the test, the sheet was evaluated as "○" if it satisfied all of the following requirements 1 to 3, as "△" if it satisfied two of the requirements 1 to 3, and as "×" if it satisfied one of the requirements 1 to 3 or none of them. Gypsum board was used as the non-combustible substrate. 1. Total calorific value is 8MJ / m 2 below 2. The maximum heat generation rate is 200kW / m for 10 seconds or more. 2 Not to exceed 3. No cracks or holes that penetrate to the back surface and are harmful to fire resistance

[0097] (c) Sheet hardness The sheet hardness of the laminated sheets of each Example and Comparative Example was evaluated by a scratch hardness (pencil method) test in accordance with JIS K 5600-5-4. The sheet hardness was evaluated by scratching the surface of the laminated sheet with a pencil and visually checking whether the laminated sheet was torn. In the test, the laminated sheet was evaluated as "○" when no significant defects occurred on the surface, "△" when defects occurred on the surface of the laminated sheet but did not cause problems in use, and "×" when significant defects occurred on the surface of the laminated sheet.

[0098] (d) Smoothness In the manufacturing process of the laminated sheet of each Example and Comparative Example, when applying the anchor material (urethane resin containing vinyl chloride acetate), the surface formation state of the original fabric layer or the first original fabric layer and the second original fabric layer was visually confirmed to evaluate the smoothness of the original fabric layer. In the evaluation, the case where the plate clogging due to powder falling of the inorganic material from the original fabric layer did not occur and it was possible to form a uniform coated surface without unevenness or omissions was evaluated as "○", the case where the plate clogging, unevenness, or omissions due to powder falling occurred due to the printing conditions or lamination conditions was evaluated as "△", and the case where the plate clogging due to powder falling occurred or it was extremely difficult to form a uniform coated surface was evaluated as "×".

[0099] (e) Powdery surface In the manufacturing process of the laminated sheet of each Example and Comparative Example, the surface of the original layer or the surface of the laminated first original layer and second original layer was dry rubbed by hand, and the presence or absence of powdering or falling off of the inorganic material (calcium carbonate or silica) was visually evaluated. In the evaluation, the case where no inorganic particles were confirmed on the surface of the hand was evaluated as "○", the case where the inorganic material was confirmed on the surface of the hand was evaluated as "△", and the case where the inorganic material was confirmed over the entire surface of the hand was evaluated as "×".

[0100] (f) Ink adhesion In the manufacturing process of the laminated sheet of each Example and Comparative Example, Nichiban cellophane tape was pressed onto the surface of the original fabric layer (second original fabric layer) after the formation of the picture pattern layer, and then peeled off with a force of 10 N, and the presence or absence of peeling inside the picture pattern layer or between the original fabric layer and the picture pattern layer was visually evaluated. In the evaluation, the case where no peeling occurred inside the picture pattern layer or between the original fabric layer and the picture pattern layer was evaluated as "○", the case where peeling occurred inside the picture pattern layer or in part between the original fabric layer and the picture pattern layer was evaluated as "△", and the case where the picture pattern layer was attached to the entire surface of the cellophane tape and significant peeling occurred inside the picture pattern layer or between the original fabric layer and the picture pattern layer was evaluated as "×".

[0101] (g) Processability When the laminated sheets of each Example and Comparative Example were folded and then opened again, the presence or absence of cracks or powder falling off at the folded portion was visually evaluated. In the evaluation, the case where no cracks or powder falling off occurred at the folded portion was marked as "○", the case where slight cracks or powder falling off occurred at the folded portion was marked as "△", and the case where cracks or powder falling off significantly occurred at the folded portion was marked as "×". The configurations of the respective Examples and Comparative Examples are summarized in Table 1. The evaluation results of the respective Examples and Comparative Examples are summarized in Table 2.

[0102] [Table 1]

[0103] [Table 2]

[0104] As shown in Table 1, the laminated sheets of each embodiment, which contain inorganic particles in the original fabric layer or the first original fabric layer and the second original fabric layer, and have anchor layers on the surfaces of the original fabric layer or the first original fabric layer and the second original fabric layer, did not receive an "X" rating for interlayer adhesion, non-flammability, or sheet hardness, and were able to achieve a balance between each characteristic. On the other hand, in the laminate sheets of each comparative example in which the original fabric layer or at least one of the first and second original fabric layers did not contain inorganic particles, or an anchor layer was not provided on the surface of the original fabric layer or the first and second original fabric layers, at least one of the interlayer adhesion, non-flammability, and sheet hardness was rated as "X".

[0105] Furthermore, the laminate sheets of Examples 1 to 3, in which the inorganic material contained in the first raw layer has an average particle size of 2 μm and a content of 50 mass%, were smoother and less prone to powdering of the inorganic material than the laminate sheet of Example 4, in which the inorganic material has an average particle size of 4 μm, and the laminate sheet of Example 5, in which the inorganic material content is 95 mass%. Furthermore, the laminate sheets of Examples 1 to 3 had higher ink adhesion and processability than the laminate sheet of Example 5, in which the inorganic material content is 95 mass%. On the other hand, the laminate sheets of Examples 1 to 3 had higher non-combustibility and sheet hardness than the laminate sheet of Example 6 in which the content of the inorganic material was 5% by mass.

[0106] Furthermore, the laminated sheets of Examples 2 and 3, in which the average particle size of the inorganic material contained in the second raw layer was 2 μm and the content was 40 mass%, were smoother, less susceptible to powdering of the inorganic material, and had higher processability than the laminated sheet of Example 7, in which the average particle size of the inorganic material was 5 μm, and the laminated sheet of Example 8, in which the content of the inorganic material was 60 mass%.

[0107] Furthermore, the laminated sheets of Examples 2 and 3, in which the thickness ratio of the first original fabric layer to the second original fabric layer was 60:40, had higher non-flammability, sheet hardness and processability than the laminated sheet of Example 9, in which the thickness ratio of the first original fabric layer to the second original fabric layer was 25:75.

[0108] From the above evaluation results, it was confirmed that a laminate sheet containing an inorganic material in the original fabric layers (first original fabric layer and second original fabric layer) and having an anchor layer has higher interlayer adhesion, non-flammability and sheet hardness compared to a laminate sheet not containing an inorganic material in the original fabric layers or not having an anchor layer.

[0109] The scope of the present disclosure is not limited to the exemplary embodiments shown and described, but includes all embodiments that achieve equivalent effects to those contemplated by the present disclosure. Furthermore, the scope of the present disclosure is not limited to the combination of inventive features defined by the claims, but may be defined by any desired combination of specific features among all the respective disclosed features. [Explanation of symbols]

[0110] 1,2,3 laminated sheet 11 Adhesive layer 12 Original layer 12a Inorganic materials 12b void 13 Pattern layer 14 Surface protective layer 16a, 16b Anchor layer 22 Original layer 22a First fabric layer 22b Second primary fabric layer 26a~26d Anchor layer 34 Surface protective layer 34a Upper resin layer 34b First topcoat layer 34c Second topcoat layer

Claims

1. A raw fabric layer including a resin material and an inorganic material; An anchor layer formed on both sides of the raw fabric layer; a surface protective layer formed on a surface of the anchor layer opposite to a surface on which the base fabric layer is provided; Equipped with The anchor layer does not include an inorganic material, The raw fabric layer has a first raw fabric layer and a second raw fabric layer, The anchor layer is further formed on a surface of the first raw fabric layer on the side where the second raw fabric layer is provided and on a surface of the second raw fabric layer on the side where the first raw fabric layer is provided, The surface protective layer is formed on the upper surface of the second raw fabric layer. Laminated sheet.

2. A raw fabric layer including a resin material and an inorganic material; A surface protective layer formed on one surface of the raw fabric layer; An anchor layer formed on at least the surface of the base layer on the surface protective layer side; Equipped with The raw fabric layer has a first raw fabric layer and a second raw fabric layer, The anchor layer is further formed on a surface of the first raw fabric layer on the side where the second raw fabric layer is provided and on a surface of the second raw fabric layer on the side where the first raw fabric layer is provided, The anchor layer contains a urethane-based resin containing a copolymer of vinyl chloride and vinyl acetate or an acrylic-based resin containing a copolymer of vinyl chloride and vinyl acetate, The surface protective layer is formed on the upper surface of the second raw fabric layer. Laminated sheet.

3. A raw fabric layer including a resin material and an inorganic material; An anchor layer formed on both sides of the raw fabric layer; a surface protective layer formed on a surface of the anchor layer opposite to a surface on which the base fabric layer is provided; Equipped with The raw fabric layer has a first raw fabric layer and a second raw fabric layer, The anchor layer is further formed on a surface of the first raw fabric layer on the side where the second raw fabric layer is provided and on a surface of the second raw fabric layer on the side where the first raw fabric layer is provided, the anchor layer does not contain an inorganic material and contains a urethane-based resin containing a copolymer of vinyl chloride and vinyl acetate or an acrylic-based resin containing a copolymer of vinyl chloride and vinyl acetate; The surface protective layer is formed on the upper surface of the second raw fabric layer. Laminated sheet.

4. The base layer has a plurality of voids formed around the inorganic material, The voids are dispersed throughout the raw fabric layer. The laminate sheet according to any one of claims 1 to 3.

5. The average particle size of the inorganic material is in the range of 1 μm to 3 μm, and the maximum particle size of the inorganic material is 50 μm or less. The laminate sheet according to any one of claims 1 to 4.

6. The content of the inorganic material in the first raw fabric layer is greater than the content of the inorganic material in the second raw fabric layer. The laminate sheet according to any one of claims 1 to 5.

7. The first base layer contains at least one of calcium carbonate and a calcium carbonate salt as the inorganic material, The second raw layer contains, as the inorganic material, at least one of calcium carbonate and inorganic materials other than calcium carbonate. The laminate sheet according to any one of claims 1 to 6.

8. The content of the inorganic material relative to the total amount of the resin material and the inorganic material in the first base layer is in the range of 20% by mass or more and 90% by mass or less, The content of the inorganic material in the second raw layer with respect to the total amount of the resin material and the inorganic material is in the range of 1 mass% or more and 50 mass% or less. The laminate sheet according to any one of claims 1 to 7.

9. The ratio of the thickness of the first raw fabric layer to the thickness of the second raw fabric layer is 50:50 to 95:

5. The laminate sheet according to any one of claims 1 to 8.

10. The resin material is a thermoplastic resin, The thermoplastic resin is at least one of polypropylene, polyethylene, and polyester. The laminate sheet according to any one of claims 1 to 9.

11. In an adhesion test based on JIS K 5600-5-6, the number of squares that peel off is between 0 and 2. The laminate sheet according to any one of claims 1 to 10.

12. A method for producing a composition comprising: mixing an inorganic material and a resin material; A first resin film and a second resin film containing the inorganic material and the resin material are formed to form a first raw fabric layer and a second raw fabric layer, An anchor material not containing an inorganic material is applied to both sides of the first raw fabric layer and both sides of the second raw fabric layer to form an anchor layer; The first raw fabric layer and the second raw fabric layer are laminated to form a raw fabric layer; A method for manufacturing a laminated sheet, comprising coating a resin material on the anchor layers formed on both sides of the raw fabric layer and curing the resin material to form a surface protective layer.

13. A method for producing a composition comprising: mixing an inorganic material and a resin material; A first resin film and a second resin film containing the inorganic material and the resin material are formed to form a first raw fabric layer and a second raw fabric layer, An anchor material containing a urethane-based resin including a copolymer of vinyl chloride and vinyl acetate or an acrylic-based resin including a copolymer of vinyl chloride and vinyl acetate is applied to at least one of the surface of the first raw fabric layer opposite to the second raw fabric layer and the surface of the second raw fabric layer opposite to the first raw fabric layer, and the surface of the first raw fabric layer on the second raw fabric layer side and the surface of the second raw fabric layer on the first raw fabric layer side, to form an anchor layer; The first raw fabric layer and the second raw fabric layer are laminated to form a raw fabric layer; A resin material is applied onto the anchor layer formed on the surface of the base layer, and then cured to form a surface protective layer. A method for manufacturing a laminated sheet.

14. A method for producing a composition comprising: mixing an inorganic material and a resin material; A first resin film and a second resin film containing the inorganic material and the resin material are formed to form a first raw fabric layer and a second raw fabric layer, An anchor material containing no inorganic material and a urethane-based resin containing a copolymer of vinyl chloride and vinyl acetate or an acrylic-based resin containing a copolymer of vinyl chloride and vinyl acetate is applied to both sides of the first raw fabric layer and both sides of the second raw fabric layer to form an anchor layer; The first raw fabric layer and the second raw fabric layer are laminated to form a raw fabric layer; A method for manufacturing a laminated sheet, comprising coating a resin material on the anchor layers formed on both sides of the raw fabric layer and curing the resin material to form a surface protective layer.

Citation Information

Patent Citations

  • Decorative sheet

    JP1997277483A

  • Phosphorescent light-emitting adhesive tape and sheet

    JP1999241052A

  • Decorative sheet

    JP2000326451A

  • Optical reflector and surface light source device

    JP2005004195A

  • Decorative sash

    JP2009097138A